2018
DOI: 10.1186/s13638-018-1177-3
|View full text |Cite
|
Sign up to set email alerts
|

An extension of the RiMAX multipath estimation algorithm for ultra-wideband channel modeling

Abstract: This work presents an extension of the high-resolution RiMAX multipath estimation algorithm, enabling the analysis of frequency-dependent propagation parameters for ultra-wideband (UWB) channel modeling. Since RiMAX is a narrowband algorithm, it does not account for the frequency-dependency of the radio channel or the environment. As such, the impact of certain materials in which these systems operate can no longer be considered constant with respect to frequency, preventing an accurate estimation of multipath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…However, in [139], DMC has been demonstrated to contribute significantly to the total received power in NLoS condition at mmWave bands, and the contribution of DMC can be higher with increasing frequency. In the cm-wave band (3.1 GHz to 10.6 GHz), [112] observed that the DMC power ratio decreases with increasing frequency. At present, there is no unified conclusion on the relationship between DMC and frequency, therefore, it still needs further study.…”
Section: Referencementioning
confidence: 95%
See 2 more Smart Citations
“…However, in [139], DMC has been demonstrated to contribute significantly to the total received power in NLoS condition at mmWave bands, and the contribution of DMC can be higher with increasing frequency. In the cm-wave band (3.1 GHz to 10.6 GHz), [112] observed that the DMC power ratio decreases with increasing frequency. At present, there is no unified conclusion on the relationship between DMC and frequency, therefore, it still needs further study.…”
Section: Referencementioning
confidence: 95%
“…More detailed information on RiMAX can be found in [4], and the influences of incomplete and inaccurate data models on RiMAX are discussed in [15]. Based on the RiMAX algorithm framework, several extensions have been made for joint estimation of DMC parameters in frequency, angular, as well as polarization domains [21], [112].…”
Section: A Maximum Likelihood Estimation Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saito et al (2016) evaluated the multipath effect in the line-of-site (LOS) condition, distinguishing the directional and polarisation characteristics estimated by the RiMax algorithm proposed in Hanssens et al (2018). Mrstik et al (2007) quantitatively analysed the effect of angle of inclination between the Wi-Fi station and Wi-Fi AP in tracking using RADAR.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the antenna array responses of transmitter and receiver will no longer be frequency-independent, and can vary significantly over the total UWB bandwidth. In order to track these frequency-dependent propagation parameters, an extension to the RiMAX framework was developed that can process UWB measurement data, and will be referred to as UWB-RiMAX from now on [21]. This framework is described in Algorithm 1, and depicted in Figure 4.…”
Section: A Uwb-rimax Algorithm (Figure 3 Block 2)mentioning
confidence: 99%